2017
DOI: 10.24127/gdn.v7i1.724
|View full text |Cite
|
Sign up to set email alerts
|

Hope of Success and Fear of Failure Predicting Academic Procrastination Students Who Working on a Thesis

Abstract: Abstract:Students, who are working on the thesis, have some difficulties caused by internal and external factors. Those problems can disrupt the completion of their thesis, such as the tendency to do academic procrastination. Increasing achievement motivation can reduce academic procrastination. This study aims to look at the role of achievement motivation (hope of success and fear of failure) in predicting academic procrastination. The study used a quantitative approach by distributing academic procrastinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 3 publications
1
7
0
5
Order By: Relevance
“…Research on fear of failure on academic procrastination had been conducted by previous researchers. The results of this study were in accordance with previous research by Akmal et al, (2017) which explained that the feeling of fear of failure increasingly played a role in giving rise to academic procrastination. The existence of a positive relationship between fear of failure and academic procrastination causes the higher the fear of failure, the greater the tendency of students to show academic procrastination behavior.…”
Section: Effect Of Fear Of Failure On Academic Procrastinationsupporting
confidence: 92%
See 1 more Smart Citation
“…Research on fear of failure on academic procrastination had been conducted by previous researchers. The results of this study were in accordance with previous research by Akmal et al, (2017) which explained that the feeling of fear of failure increasingly played a role in giving rise to academic procrastination. The existence of a positive relationship between fear of failure and academic procrastination causes the higher the fear of failure, the greater the tendency of students to show academic procrastination behavior.…”
Section: Effect Of Fear Of Failure On Academic Procrastinationsupporting
confidence: 92%
“…Research results by Zarrin and Gracia (2020); Akmal et al, (2017) revealed that fear of failure is increasingly playing a role in bringing up academic procrastination behavior. The higher the fear of failure is, the greater the procrastination behavior shown by students.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Akmal, Arlinkasari & Fitriani (2017) on students who are compiling the thesis shows a positive influence between the hope of success and fear of failure with academic procrastination. If students have a high fear of failure, then academic procrastination will also be higher, and vice versa.…”
Section: Results Discussionmentioning
confidence: 99%
“…Fear of failure juga memiliki pengaruh terhadap prokrastinasi akademik (Akmal et al, 2017). Sampel pada penelitian tersebut terdiri dari 182 mahasiswa yang sedang mengerjakan skripsi dan berkuliah di daerah Jakarta.…”
unclassified
“…Semakin tinggi fear of failure pada mahasiswa, maka semakin besar kecenderungan untuk menunjukkan perilaku prokrastinasi akademik. Sementara itu, semakin tinggi harapan mahasiswa untuk berhasil dalam mengerjakan skripsi maka mahasiswa akan cenderung menampilkan sedikit prokrastinasi akademik (Akmal et al, 2017).…”
unclassified